Dux Bellorum - Johnson, Flint F. (Studia Celtica Posnaniensia, 2020)
This paper will explore the accuracy and intent of the term dux bellorum, leader of war, as used in the Historia Brittonum with regards to Arthur. A discussion of Post-Roman archaeology, supplemented with contemporary historical documents, will establish that no Roman commands, such as the dux Britanniarum or comes Britanniarum, survived into the “Arthurian” period of the late fifth or early sixth centuries. A broader search of historical records will indicate that a linguistic cognate of dux bellorum was twice conferred on Celtic kings when leading a coalition of tribes in times of mutual threat according to the historical record; one was known to the author of the Historia Brittonum. A review of Historia Brittonum scholarship will show it came to its present form in c. 829 Gwynedd, ruled at the time by Merfyn Frych. The contemporary historical context was that the British kingdoms had been pressured for decades by the English and were specifically invaded by Wessex at around this time. This will be followed by a discussion of several biases in the history including a focus on Gwynedd’s dynasties and Merfyn in particular and British success against the English when united and failure when they were divided. Arthur was the best example of the latter agenda and because of this the most likely example of what Merfyn hoped to create. A summary of Merfyn’s political career in this context can be used to explain Arthur’s entire description in the work.